Distribution and cycling of dimethylsulfide (DMS) and dimethylsulfoniopropionate (DMSP) in the sea-surface microlayer of the Yellow Sea, China, in spring - Zhang, Hong-Hai; Yang, Gui-Peng; Zhu, Tong (Continental Shelf Research, 2008)
The distributions of dimethylsulfide (DMS) and its precursor, dimethylsulfoniopropionate (DMSP), were examined in the surface microlayer and corresponding subsurface water of the Yellow Sea, China, in April 2006. The average concentrations of DIVIS and DMSP of dissolved (DMSPd) and particulate (DMSPp) forms were 5.42 (1.78-12.75), 9.22 (2.85-19.73) and 17.50 (4.33-36.09) nmol L-1 in the subsurface water, and those in the surface microlayer were 4.92 (1.69-10.66), 17.08 (3.13-38.82) and 22.54 (4.85-47.24) nmol L-1, respectively. The enrichment factor (EF) of DMS in the microlayer ranged from 0.47 to 2.24 with a mean of 0.98. In contrast, DMSPd and DMSPp appeared to be enriched in the microlayer with average El's of 1.98 and 1.39, respectively. A close correlation of integrated DMS, DMSPp and chlorophyll a concentrations for compiled data from all stations in the microlayer and the subsurface water indicated that phytoplankton biomass might play an important role in controlling the distributions of biogenic sulfurs in the study area. Moreover, a statistically significant relationship was found between the microlayer concentrations of DMS, DMSP and chlorophyll a and their subsurface water concentrations, suggesting a close linkage between these two water compartments. Interestingly, we observed higher biological production rates and consumption rates of DMS in the microlayer relative to the subsurface water. Furthermore, the DMS production rates were closely correlated both with DMSPd and chlorophyll a concentrations. Our study showed that the major sink of DMS in microlayer was escape into the atmosphere, which greatly exceeded its bacterial consumption. A preliminary estimate for average flux of DIVIS from the Yellow Sea to the atmosphere was 6.41 mu mol m(-2) d(-1) during spring. (C) 2008 Elsevier Ltd. All rights reserved. Oceanography SCI(E) 0 ARTICLE 17 2417-2427 28